How do circadian rhythms and neural synchrony shape networked cooperation? - Vasiliauskaite, Vaiva; Hausladen, Carina I. (Frontiers in Physics, 2023)
This study investigates the effects of temporal changes at the individual and social levels and their impact on cooperation in social networks. A theoretical framework is proposed to explain the probability of cooperation as a function of endogenously driven periodic temporal variation and neural synchrony modeled as a diffusion process. Agents are simulated playing a prisoner’s dilemma game, with and without evolution, in a two-player setting and on networks. Most importantly, we find that temporal variation and synchrony influence cooperation patterns in a non-trivial way and can enhance or suppress cooperation, depending on exact parameter values. Furthermore, some of our results point to promising future research on human subjects. Specifically, we find that cooperators can dramatically increase their payoff—as opposed to defectors—if neural synchrony is present. Furthermore, the more heterogeneous the synchrony between two agents, the less they cooperate. In a network setting, neural synchrony inhibits cooperation, and variation in circadian patterns counteracts this effect. Call: Hidden Order Behind Cooperation in Social Systems.